THE INFLUENCE OF FARMERS' SOCIO-ECONOMIC FACTORS ON THE PRODUCTIVITY AND INCOME OF MUNG BEAN FARMING IN WEWIKU DISTRICT, MALAKA REGENCY - Anggita Natalia Talomanafe; Damianus Adar; Yakobus C.W. Siubelan (Buletin Ilmiah Impas, 2026)
This study held in Weoe Village, District Wewiku, Malaka Regency. Research This aim For analyze size productivity, income, and influence factor social economy farmer to productivity farming peanut green. The research method used is method survey with determination location by purposive sampling and determination respondents use simple random sampling method. Data collected through interviews, observations, questionnaires, and documentation, then analyzed use analysis productivity, income, and multiple linear regression. Research results show that the average productivity farming peanut green in the area study not optimal between farmer that is around 887kg/ha, condition This show that productivity in the region study influenced by several things, such as Not yet existence use fertilizer, control pests and diseases that still exist limited, limitations seed superior, and technique cultivation that is still depends on the method traditional. Average income farming peanut green namely Rp.6,665,795, obtained from difference between total revenue of Rp. 7,995,837 and total costs production issued by farmers​ in One season planting Rp. 1.330,058. Analysis results multiple linear regression show that factor social economy farmer in a way simultaneous influential to productivity and income farming peanut green, whereas in a way partial there is a number of influential variables​ real and some variables other No influential real to productivity and income. With Thus, the increase productivity and income farming peanut green can done through management factor more optimal production and​ improvement knowledge and skills farmer in activity farming.